An ABA–ROP toggle switch orchestrates xylem differentiation and cell wall patterning - Valentina Elettra Alberti; Daria Bloch; Erik Gengel; Mallikarjuna Rao Puli; Limor Poraty-Gavra; Shaul Yalovsky (Proceedings of the National Academy of Sciences, 2025)
The mutual antagonistic signaling of abscisic acid (ABA) and ROP GTPases highlights an intersection between stress responses and pattern formation. Previously, we have shown that signaling of ABA in the endodermis leads to protoxylem (PX) differentiation. In this study, we demonstrate that ROPs suppress PX differentiation in the roots of both Arabidopsis and tomato. Fourier transform and Shannon’s entropy show that endodermal ABA signaling controls the periodicity and overall order of PX secondary cell wall (SCW) coils in an ROP-dependent manner. Correspondingly, in the PX, GFP-ROP11 is initially dispersed and gradually becomes distributed in an oscillatory fashion with a periodicity corresponding to that of the SCW coils. Oryzalin treatments disrupt the frequency and increase the entropy of the GFP-ROP11 signal, suggesting that microtubules delimit ROP distribution. Signaling of ABA in the endodermis encourages the enlargement of metaxylem SCW pits, while ABA signaling in the stele limits this enlargement. Pit size and density are decreased in ROP mutants while ABA enhances ROP11 expression in the stele and broadens its distribution in the endodermis. Taken together, non-cell-autonomous and cell-autonomous interactions between ABA and ROPs regulate xylem differentiation and SCW patterning.